Teater Koma's Dramaturgical Strategy in Delivering Social Criticism of the New Order Era - Mawardi, Taufik; Jufry, Fara Dayana Mohd (Global Journal of Social Learning, 2025)
This study examines the dramaturgical strategies employed by Teater Koma to convey social criticism during the New Order era, a period marked by stringent political censorship that constrained artistic expression. Focusing on a case study of the 1985 performance of Opera Kecoa, this research analyzes how dramaturgical components such as the script, characterization, symbolism, and satirical humor are strategically utilized to articulate social and political injustices. Employing a qualitative methodology, the study draws upon text analysis and performance documentation to explore these elements in depth. The findings reveal that Teater Koma creatively circumvented censorship through the use of symbolic language, allegorical storytelling, and nuanced narrative structures, enabling the theater to raise public awareness without directly contravening the political restrictions of the time. This dramaturgical approach functioned not only as an artistic expression but also as a subtle form of resistance against authoritarian suppression. The study underscores the critical role of theater as a medium for socially engaged discourse and political critique within repressive regimes.